2018
DOI: 10.1016/j.ultsonch.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of tip sonication effects on structural quality of graphene nanoplatelets (GNPs) for superior solvent dispersion

Abstract: The exceptional properties of graphene and its structural uniqueness can improve the performance of nanocomposites if it can attain the uniform dispersion. Tip sonication assisted graphene solvent dispersion has been emerged as an efficient approach but it can cause significant degradation of graphene structure. This study aimed to evaluate the parametric influence of tip sonication on the characteristics of sp carbon structure in graphene nanoplatelets by varying the sonication time and respective energy at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 70 publications
4
51
0
1
Order By: Relevance
“…Porous graphene oxide is indeed well known to be have reduced area compared the pristine GO and also an higher amount of defects, which makes the nanofiller intrinsically more permeable: Lee et al [ 67 ] demonstrated the formation of pores upon GO, and most likely, such treatment was also able to partially fracture the sheets themselves. On the other hand, fragmentation of GO platelet during PEAGO synthesis can likely be related to the presence of intensive mixing and sonication, which could produce mechanical stresses able to break GO and PEAGO sheets, as demonstrated also by Baig et al [ 72 ].…”
Section: Resultsmentioning
confidence: 93%
“…Porous graphene oxide is indeed well known to be have reduced area compared the pristine GO and also an higher amount of defects, which makes the nanofiller intrinsically more permeable: Lee et al [ 67 ] demonstrated the formation of pores upon GO, and most likely, such treatment was also able to partially fracture the sheets themselves. On the other hand, fragmentation of GO platelet during PEAGO synthesis can likely be related to the presence of intensive mixing and sonication, which could produce mechanical stresses able to break GO and PEAGO sheets, as demonstrated also by Baig et al [ 72 ].…”
Section: Resultsmentioning
confidence: 93%
“…Under these mild mixing conditions, negligible structural damage is expected for the CNTs and GNPs. The Raman spectroscopy ( Figure 4) was carried out on CNTs and GNPs using laser excitation with wavelength 532 nm to avoid adverse effects on CNMs structural quality such as edge-type defect, reduction of aspect ratio and sp2 domain crystallinity (La), that cause a deleterious influence on their mechanical and electrical properties [34,35].…”
Section: Carbon Nanotube (Cnt) + Graphene Nanoplatelet (Gnp) Dispersimentioning
confidence: 99%
“…Acoustic cavitation produced during TS promotes highly intense local conditions characterised by short-lifetime hot spots whose temperature rises to 5000°C, reaching pressure values of around 1000 atm, and cooling rates of 10 10 KÁs -1 [60]. Even though propagation of ultrasonic waves in liquids is generally considered as an adiabatic process because of the rapid pressure variation [61], the highly intense local conditions can cause ceramic, metallic, carbonaceous, and polymeric particles to experience, according to their nature, changes of their molecular weight, chemical and crystalline structure, and morphology [32,33,[61][62][63][64][65][66][67]. Hence, the first step was to determine the effects of TS on PEEK particles.…”
Section: Effect Of Tip Ultrasonication On the Peek Particlesmentioning
confidence: 99%